EFL Students’ Perspective on Language Cross-study: - - Arjulayana, Arjulayana; Rohimah, Elsa; Kintamani, Suci; Hidayah, Siti Nur; Ramadhan, Intan Rizqi (Journal of English Education and Teaching, 2024)
Cross-study is an important activity to improve the quality of education and infrastructure in educational institutions with the aim of adding insight and knowledge that will be applied in the future to be better. it also provides an opportunity for students to experience different atmospheres and learning methods, as well as for students to have the passion and enthusiasm in gaining quality learning ways, especially in English, and create new relationships between students of muhamadiyah university. This study is aimed to explore student’s perceptions of cross-language study in educational contexts. The methode of this research is qualitative descriptive By involving 42 students as respondents, the data collection through a survey and interview which included several questions related to the benefits of cross-language study. The research results show that 98% of the majority respondents have a very positive perception of the benefits of cross-language studies as the representation of social interaction in digital age. They consider cross-language study have a significant impact on their personal and students language improvements, such as listening, and speaking, as well as broadening their understanding of linguistics and cultural diversity. These results demonstrate the importance of cross- language education in increasing understanding of cultural and linguistic diversity, as well as preparing students for future global challenges.